Leveraging the Energy Transition for greater black entrepreneurial participation in the Liquid Fuels sector in South Africa - Tlou, Dineo (University of the Witwatersrand, Johannesburg, 2023)
Background: The Liquid Fuels Industry in South Africa is a key contributor to the economy and development agenda of the country. The industry has been dominated by large multinational and privately-owned companies that control and own some of the factors of production. Purpose: This study aims to examine how the energy transition can be leveraged for greater Black entrepreneurial participation in the liquid fuels sector in South Africa. Design, methodology and approach: A qualitative study was conducted, and primary data was collected using semi-structured interviews with 14 Black entrepreneurs engaged in the liquid fuels sector; primarily sourced through the National Energy Wholesalers Association of South Africa (NAEWASA) and the South Africa Petroleum Industry Association of South Africa (SAPIA) as well as 4 active and former Black business executives in the liquid fuels industry. A combined total of 18 interviews was conducted. The method of analysis employed was thematic analysis to allow for further probing of participants. Findings: The results indicate that Black entrepreneurs in the liquid fuels sector were aware of the energy transition, related activities as well as potential opportunities. They were, however, of the view that it was premature for South Africa considering the structural challenges. Business executives expressed a similar understanding of the energy transition but were aligned in that it needed to be paced for each country. Additionally, entrepreneurs experienced barriers to participation that impede their ability to be active participants in the sector. The results also indicate that the sector has skills requirements to enable entrepreneurial participation in the Energy Transition
A research report submitted in partial fulfillment of the requirements for the degree of Master of Management in Energy Leadership to the Faculty of Commerce, Law and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2023
Keywords: Liquid Fuels Sector; Energy Transition; Entrepreneurial opportunities; Just Energy Transition; Skills requirements; UCTD; SDG-8: Decent work and economic growth